The triumph of anti-art : conceptual and performance art in the formation of post-modernism - McEvilley, Thomas (McPherson & Co, 2005)
From roughly 1965 to 1980, Conceptual Art and Performance Art took center stage throughout the western world, introducing new and complex ideas to the practice of contemporary art which reverberate to this day. Thomas McEvilley's The Triumph of Anti-Art not only explains the origins of these controversial and compelling art forms, but also uncovers many relatively unrecognized yet indisputably important artists, American and European. He guides the reader through a thicket of seemingly arcane meanings of these nonrepresentational art form, and brings clarity to the intentions and agendas of these artists, as well as to their real world contexts. The long-term effects of "anti-art," and the development of the pluralistic situation known as post-Modernism, are described in vivid detail. From the Greek philosopher Diogenes, through the 19th-century German romantic tradition, to the modern art critic Clement Greenberg, McEvilley traces philosophical ideas and political impulses that temporarily led to a toppling of painting and sculpture in the decades right after World War II. Following an overview of Modernism and Marcel Duchamp's influence, a chapter on Yves Klein sets the state for surveys of Conceptual Art and its practitioners, including Bernar Venet, John Baldessari, and Francis Alys. McEvilley then gives equal focus to Performance Art with chapters on Andy Warhol, Brian O'Doherty, and Marina Abramovic and Ulay, among others. At the end of the volume the "triumph" of "anti-art" is explored in depth, as are the origins of the terms, practices, and politics of global art history.